2010
DOI: 10.1136/jnnp.2010.226340.168
|View full text |Cite
|
Sign up to set email alerts
|

POMD08 Zebrafish models for early onset Parkinson's disease

Abstract: BackgroundZebrafish are a vertebrate animal model system which is highly amenable for drug screens. Autosomal recessively inherited, loss of function mutations in the PTEN-induced kinase 1 (pink1) gene are one cause of early-onset Parkinson's disease (PD).Objectives(1) To establish a stable pink1 mutant zebrafish line and determine whether this pink1 mutant line shares crucial characteristics with human pink1-mutant patients, in particular loss of dopaminergic neurones and impaired mitochondrial function. (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A later model corroborated these findings, as well as noting weight loss and a mild movement deficit [23]. Additional PINK1 mutant models have been produced in Caenorhabditis elegans, where increased susceptibility to oxidative stress and mitochondrial morphology defects were observed [24], as well as in Danio rerio, which exhibit a decrease in dopamine-producing cells and reduced mitochondrial activity [25].…”
Section: Genetic Analysis Of Pink1 Functionmentioning
confidence: 68%
“…A later model corroborated these findings, as well as noting weight loss and a mild movement deficit [23]. Additional PINK1 mutant models have been produced in Caenorhabditis elegans, where increased susceptibility to oxidative stress and mitochondrial morphology defects were observed [24], as well as in Danio rerio, which exhibit a decrease in dopamine-producing cells and reduced mitochondrial activity [25].…”
Section: Genetic Analysis Of Pink1 Functionmentioning
confidence: 68%
“…In addition, they can implement large-scale gene mutation and screening. These features make small animal models important in life science researches in the study of functional genomics era [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine if this is indeed the case, stable knockout lines of both pink1 and park2 are required. Bandmann et al 121 have reported the discovery of a pink1 mutant by TILLING. This mutant has a premature stop codon in exon 7 (Y431X).…”
Section: Disease-induced Mitophagic Defects: Pink1 and Park2mentioning
confidence: 99%
“…This suggests that Gsk3b may play a role in the peripheral phenotypes observed, but that other factors are involved in the dopamine neuron loss. Further study of Wnt signaling, the known pink1 mutant 121 and generation of another pink1 knockout model is therefore recommended.…”
Section: Manipulations Of Park2 In Zebrafishmentioning
confidence: 99%